1996
DOI: 10.1111/j.1601-0825.1996.tb00202.x
|View full text |Cite
|
Sign up to set email alerts
|

The periodontal health of homosexual men with HIV infection: a controlled study

Abstract: OBJECTIVE Identify types, prevalence and severity of periodontal changes associated with HIV infection. DESIGN: Cross‐sectional controlled blinded study. SETTING: Open access genito‐urinary medicine clinic. PARTICIPANTS: Convenience sample of 794 homosexual men aged 18–65. OUTCOME MEASURES: Prevalence, extent and severity of probing attachment loss (PAL), pocketing, gingival ulceration, gingivitis, bleeding on probing (BOP), gingival red bands and diffuse and punctate erythema of the attached gingiva (selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
1
7

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 24 publications
7
38
1
7
Order By: Relevance
“…The epidemiological validity of the Ramfjord teeth in representing the periodontal status of the whole mouth has previously been established [23-28]. Although we are mindful of the limitations of partial mouth measurements such as the underestimation of both the extent and prevalence of periodontal disease reported in some studies [27,31] and the bias reported in others [29,30,32], with measurement of sites on the buccal side of the tooth reported to show better reliability than measurement on the lingual side because of better visibility to the examiner, assessment of the Ramfjord teeth was found to reduce time, cost, patient, and examiner fatigue, while also providing a practical alternative to the 168 measurements for each clinical parameter required to characterise the prevalence and severity of periodontal disease in a single whole mouth using full mouth assessment [27]. …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The epidemiological validity of the Ramfjord teeth in representing the periodontal status of the whole mouth has previously been established [23-28]. Although we are mindful of the limitations of partial mouth measurements such as the underestimation of both the extent and prevalence of periodontal disease reported in some studies [27,31] and the bias reported in others [29,30,32], with measurement of sites on the buccal side of the tooth reported to show better reliability than measurement on the lingual side because of better visibility to the examiner, assessment of the Ramfjord teeth was found to reduce time, cost, patient, and examiner fatigue, while also providing a practical alternative to the 168 measurements for each clinical parameter required to characterise the prevalence and severity of periodontal disease in a single whole mouth using full mouth assessment [27]. …”
Section: Discussionmentioning
confidence: 96%
“…Moreover only 39 patients were used in their study compared to the present study with a sample size of 120. Robinson et al [32] also reported an association of clinical attachment destruction with progressive HIV infection but not with probing depth. It is generally expected that the lower the immunosuppression of an individual, the higher the severity of periodontal disease detected [21].…”
Section: Discussionmentioning
confidence: 99%
“…Robinson et al [4] reported a higher prevalence of chronic gingivitis and adult periodontitis in HIV-infected individuals. They also reported an increased risk of periodontal attachment loss and gingival recession without increase in pocket depth.…”
Section: Discussionmentioning
confidence: 98%
“…The association of between HIV infection and gingivitis, pocket depth, and attachment loss has been shown to be independent of other known risk factors for periodontal diseases, such as age, subgingival biofilm, and smoking. [4] Lamster et al, [5] theorized that persons with different behavioral risk factors, and thus lifestyles, may present with different clinical manifestation of the HIV disease.…”
Section: Introductionmentioning
confidence: 99%
“…This considerable variation can be due to lack of clear diagnosis standardization and the heterogeneity of the population's studies. The existence of Linear Erythematous Gingivitis as a periodontal disease entity that is strongly associated with HIV has been questioned by someand others suggested that Linear Erythematous Gingivitis is mostly misdiagnosed as gingivitis 11,12,13 .…”
Section: Linear Erythematous Gingivitismentioning
confidence: 99%